Associations between cognitive function and lifestyle factors in healthy Japanese middle-aged and older adults: A cross-sectional study - Koki Tsuda; Kotatsu Bito; Masanobu Hibi; Takahiro Ono; Hiroshi Maruyama (PLoS ONE, 2026)
The objective of this study is to comprehensively investigate associations between cognitive function and lifestyle factors. We analyzed data from a cross-sectional study of Japanese adults that included approximately 1,800 variables (e.g., physical characteristics, body composition, and lifestyle habits) and cognitive function assessed using CNS Vital Signs. For participants aged 40 years or older ( n = 710), we performed partial correlation analysis and analysis of covariance adjusted for sex, age, and years of education. Given the large number of variables, we controlled the false discovery rate within predefined data types (real, positive, ordered categorical, categorical) using the Benjamini–Hochberg procedure. We adjusted p -values to q -values and identified variables with q < 0.1 for exploratory purposes. In total, 28 variables met this criterion, with particularly prominent associations for gait characteristics, vascular function, grip strength, and oral conditions, whereas blood components and other general biomarkers did not meet the threshold. These exploratory findings identify candidate correlates of cognitive function in this relatively healthy, primarily urban Japanese cohort and require confirmation in independent longitudinal studies.